Global, regional, and national burdens of PUD in women of reproductive age from 1992 to 2021: a trend analysis based on the global burden of disease study 2021 - Wang, Xiaofeng; Yang, Song; Zhao, Shanzhi; Yang, Zhitao; Mao, Enqiang; Chen, Erzhen; Chen, Ying (Frontiers in Global Women's Health, 2025)
BackgroundPeptic ulcer disease (PUD) constitutes a significant global health concern, particularly in women of childbearing age (WCBA), who face elevated risks of severe pregnancy-associated complications. This investigation aimed to map the temporal dynamics and forecast the future incidence of PUD in this demographic to inform targeted prevention and control initiatives.MethodsThis analysis drew on the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, extracting data on PUD incidence and mortality across seven age groups (15–49 years) in WCBA. Age-standardized incidence and mortality rates were calculated using the direct method of age standardization. Temporal trends from 1992 to 2021 were analyzed using joinpoint regression. The study further employed age-period-cohort analysis to discriminate the effects of these variables on incidence and mortality, and frontier analysis to evaluate potential reductions in burden by country based on developmental status. Nordpred modeling was used to project epidemiological trends up to 2044.ResultsIn 2021, the global age-standardized incidence rates (ASIR) and death rates (ASDR) for PUD among WCBA were 24.18 per 100,000 (95% CI: 14.72–36.38) and 0.54 per 100,000 (95% CI: 0.42–0.66), respectively. The highest incidence rates were observed in Oceania, while the greatest mortality rates were recorded in South Asia. Over the period from 1992 to 2021, global age-standardized mortality rates showed a significant decline. Conversely, after an initial drop, age-standardized incidence rates began to rise, with considerable regional and country-specific variation. This increase was particularly marked in regions with high Socio-demographic Index (SDI). Frontier analyses indicate that countries or regions in the middle SDI quintiles possess significant untapped potential to enhance both access to and quality of healthcare. Despite predictions of declining age-standardized incidence and mortality rates, total case numbers are expected to continue rising modestly through 2044.ConclusionsThe study underscores substantial global disparities in PUD trends in WCBA, with increasing case numbers and regional inequalities. The findings highlight the need for focused attention on high SDI regions and older WCBA cohorts to refine disease management and prevention strategies, aiding in the mitigation of PUD's public health impact.